Resonanz als das Andere der Vernunft Versuch einer Verortung im wissenschaftlichen Diskurs der Postmoderne (ENTHYMEMA, 2019)
In the course of modernisation, religious narratives have lost their unifying power. They have been replaced by human reason and its objective of acting rationally towards progress, while experiences of relationships and their inextricably linked desire for resonance are receding into the background. However, people of modern societies will not be satisfied forever with efficiency-oriented feedback alone. They await recognition from outside; they await resonance. It is not without reason that Hartmut Rosa identifies the idea of the world falling silent, of one’s desperate call for the other finding no answer, as the deepest fear that drives people today. Against this background, Christa Rohde-Dachser describes the experience of resonance as a basic human need. Initially, she refers to examples from literature which show how resonance can be found in extraordinary experiences of nature, in the self-delimitation of love relationships or in the pre-reflexive experience of God, which requires no further justification. Subsequently, the author investigates resonance experiences in the field of psychoanalysis. In the final part of her work, she deals with the experience of resonance in a pluralistic society where there are different interpretations of meaning which are equally valid.
Keywords: resonance; modernism; belief in progress; experience of delimitation; absolute loneliness